Microbial Enzymatic Degradation of Biodegradable Plastics - Roohi; Bano, Kulsoom; Kuddus, Mohammed; R. Zaheer, Mohammed; Zia, Qamar; F. Khan, Mohammed; Md. Ashraf, Ghulam; Gupta, Anamika; Aliev, Gjumrakch (Current Pharmaceutical Biotechnology, 2017)
Background: The renewable feedstock derived biodegradable plastics are important in various industries such as packaging, agricultural, paper coating, garbage bags and biomedical implants. The increasing water and waste pollution due to the available decomposition methods of plastic degradation have led to the emergence of biodegradable plastics and biological degradation with microbial (bacteria and fungi) extracellular enzymes. The microbes utilize biodegradable polymers as the substrate under starvation and in unavailability of microbial nutrients. Microbial enzymatic degradation is suitable from bioremediation point of view as no waste accumulation occurs. Methods: It is important to understand the microbial interaction and mechanism involved in the enzymatic degradation of biodegradable plastics under the influence of several environmental factors such as applied pH, thermo-stability, substrate molecular weight and/or complexity. To study the surface erosion of polymer film is another approach for hydrolytic degradation characteristion. Results: The degradation of biopolymer is associated with the production of low molecular weight monomer and generation of carbon dioxide, methane and water molecule. This review reported the degradation study of various existing biodegradable plastics along with the potent degrading microbes (bacteria and fungi). Patents available on plastic biodegradation with biotechnological significance is also summarized in this paper. Conclusion: This paper assesses that new disposal technique should be adopted for the degradation of polymers and further research is required for the economical production of biodegradable plastics along with their enzymatic degradation.
Keywords: biodegradation